1978
DOI: 10.1073/pnas.75.10.4906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anesthetics and pressure on the thermotropic behavior of multilamellar dipalmitoylphosphatidylcholine liposomes.

Abstract: The effects of gaseous anesthetics and pressure on the thermotropic behavior of multilamellar dipalmitoylphosphatidylcholine liposomes were studied by using a highsensitivity differential scanning calorimeter. It was found that halothane and enflurane decreased the transition temperature and increased the width of the transition without affecting the enthalpy change for the main gel-to-liquid crystalline transition. This emonstrated that the anesthetics decreased the degree of cooperative interaction between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
87
1

Year Published

1981
1981
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 18 publications
(14 reference statements)
19
87
1
Order By: Relevance
“…The effect of acyl chain-length (Shimsbick & McConnell, 1973;Chapman et al, 1974;Lentz et al, 1976;Mabrey & Sturtevant, 1976;Jacobs et al, 1977;Kremer et al, 1977;Lee, 1978;Marcelja & Wolf, 1979;Scott & Cheng, 1979;Freire & Snyder, 1980;Chen & Sturtevant, 1981), polar head group (Blume & Ackerman, 1974;Chapman et al, 1974;Wu & McConnell, 1975;Lentz & Litman, 1978), or perturber molecules such as anesthetics (Jain & Wu, 1977;Mountcastle et al, 1978;Heyn et al, 1981) upon the width of the phase transition, have been reported. The theory on the cooperativity of lipid phase transition in bilayer systems is inconsistent with the idea that the thermotropic phase transition of lipid bilayers follows thermodynamically first-order kinetics.…”
Section: Resultsmentioning
confidence: 95%
“…The effect of acyl chain-length (Shimsbick & McConnell, 1973;Chapman et al, 1974;Lentz et al, 1976;Mabrey & Sturtevant, 1976;Jacobs et al, 1977;Kremer et al, 1977;Lee, 1978;Marcelja & Wolf, 1979;Scott & Cheng, 1979;Freire & Snyder, 1980;Chen & Sturtevant, 1981), polar head group (Blume & Ackerman, 1974;Chapman et al, 1974;Wu & McConnell, 1975;Lentz & Litman, 1978), or perturber molecules such as anesthetics (Jain & Wu, 1977;Mountcastle et al, 1978;Heyn et al, 1981) upon the width of the phase transition, have been reported. The theory on the cooperativity of lipid phase transition in bilayer systems is inconsistent with the idea that the thermotropic phase transition of lipid bilayers follows thermodynamically first-order kinetics.…”
Section: Resultsmentioning
confidence: 95%
“…Table 2) is comparable to previous studies for the transition temperature. The value for the proportionality factor, γ, averaged over various literature values yields a mean value γ j ) 7.34‚10 -4 mL/J for DMPC MLV, 12,14,16,20,21 γ j ) 7.07‚10 -4 mL/J for DPPC MLV, 14,16,[19][20][21]39,40 and γ j ) 7.63‚10 -4 mL/J for distearoyl phosphatidylcholine MLV. 13,20 Similar numbers where found for dieladioyl phoshatidylcholine and palmitoyl oleoyl phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer ofsmall molecules from aqueous medium into lipid bilayers is a process that is undoubtedly important in biological membranes and has accordingly received much attention in recent years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As discussed by Diamond and Katz (5) and Milgram and Solomon (20), this transfer involves rate processes in addition to the equilibrium distribution of solute between aqueous and lipid phases.…”
mentioning
confidence: 99%